Intestinal anti‐tissue transglutaminase antibodies in potential coeliac disease. (3rd December 2012) - Tosco, A.; Aitoro, R.; Auricchio, R.; Ponticelli, D.; Miele, E.; Paparo, F.; Greco, L.; Troncone, R.; Maglio, M.
Summary Anti‐tissue transglutaminase 2 (anti‐TG2) antibodies are present in the serum of the great majority of untreated coeliac disease (CD) patients. They are produced and deposited in the small intestinal mucosa. Potential CD patients present serum anti‐TG2 antibodies higher than cut‐off, but a normal duodenal mucosa where mucosal deposits of anti‐TG2 are not always detectable. The aim of our work was to investigate the presence of anti‐TG2 intestinal antibodies in patients with potential CD, and identify the most sensitive test to detect them. Twelve active CD patients, 28 potential CD patients and 39 non‐CD controls were enrolled. Biopsy fragments from all patients were analysed by double immunofluorescence to detect mucosal deposits of anti‐TG2 antibodies. Fragments from the same subjects were also cultured for 24 h with medium in the presence or absence of gliadin peptides. Anti‐TG2 autoantibodies secreted into supernatants were measured by enzyme‐linked immunosorbent assay. All active CD, 68% of potential CD patients and 20% of non‐CD controls showed mucosal deposits of immunoglobulin (Ig)A anti‐TG2; at the same time 100, 96 and 8% of active CD, potential CD and non‐CD control patients secreted these antibodies in culture supernatants, respectively. Our data showed that, to detect intestinal anti‐TG2 antibodies, the measurement of antibodies secreted into culture supernatants has higher sensitivity and specificity (97·5 and 92·3%, respectively) than the detection of mucosal deposits (77·5 and 80·0%, respectively). The measurement of intestinal anti‐TG2 antibodies may prove useful in clinical practice to predict evolution towards mucosal atrophy in potential coeliac patients and identify patients with gluten sensitivity.